The ordering of sintagmatic constituents in centuries xix and xx in portuguese - Peres, Ana Carolina Teixeira [UNESP]; Pezatti, Erotilde Goreti [UNESP] (Faculdade de Letras da UFMG, 2021)
Taking as theoretical support the proposal of Pezatti (2014), which, in turn, is based on the principles of Functional Discourse Grammar, developed by Hengeveld and Mackenzie (2008), this paper aims at analyzing the ordering of interpersonal markers (grammatical and lexical) within the phrase. To this end, the corpus of the Project for the History of the Brazilian Portuguese (https://sites.google.com/site/corporaphpb) is taken as database, but more specifically private handwritten letters, reader’s letters and editor’s letters from the 19th and 20th centuries. The analyzed data reveal that, within the phrase, Operators of Mitigation, Contrast (restrictive and expansive), Exemplification and Emphasis are placed in PI; the Operator of Emphasis é que is always placed in PF and the one of Contrast apenas is usually inserted into the PI position, except in the 20th century. The lexical markers of Exemplification, Emphasis, Attitudes and Contrast (restrictive and selective) are placed into PI in most cases, with the exception the Modifiers of Exemplification for example, that is placed into PI or PF.
Ordenação de constituintes sintagmáticos no português dos séculos xix e xx
Keywords: Constituent ordering; Functional grammar; Phrase